Preparation method of electrochemical sensor of MXene / Ni / Sm-DHs nanocomposite

By combining MXene with Ni/Sm-DHs nanocomposites, MXene/Ni/Sm-DHs nanocomposites for electrochemical sensors were prepared, and the detection of nickel and samarium bimetallic hydroxides in dopamine in the prior art was solved. The problem of insufficient application in the field has achieved electrochemical sensors with high sensitivity, low detection limit and wide linear range, and is simple and safe to operate.

CN119147607APending Publication Date: 2024-12-17SHANGHAI SECOND POLYTECHNIC UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411571753.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

In the prior art, bimetallic hydroxides formed by nickel and samarium have few applications in the field of dopamine detection, and the preparation methods of composite materials are complex and the reaction conditions are harsh, making it difficult to achieve electrochemistry with high sensitivity, low detection limit and wide linear range. sensor.

Method used

MXene two-dimensional nanosheets were prepared by combining MXene with Ni/Sm-DHs nanocomposites, using mixed heating of fluoride and hydrochloric acid, and Ni/Sm-DHs materials of nanoscale spherical particles were prepared under hydrothermal conditions, and by ultrasound Stirring is made evenly dispersed between the MXene surface and layer to form MXene/Ni/Sm-DHs nanocomposite material, and finally it is used for electrode surface drop coating to prepare an electrochemical sensor.

Benefits of technology

It achieves high sensitivity, low detection limit, wide linear range and good stability, avoids nanoparticle aggregation and MXene interlayer stacking, simple and safe operation, and is suitable for dopamine detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119147607A_ABST
    Figure CN119147607A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an electrochemical sensor of an MXene / Ni / Sm-DHs nanocomposite, and relates to the technical field of sensors, the preparation method comprises the following steps: S1, preparing MXene; s2, preparing N / Sm-DHs; s3, preparation of MXene / N / Sm-DHs; s4, preparing an MXene / N / Sm-DHs electrochemical sensor; under common atmospheric pressure and room temperature, double metal hydroxides (Ni / Sm-DHs) which are non-toxic, low in cost and high in electrochemical activity are adsorbed on the surface and interlayer of MXene which is of a two-dimensional structure, large in specific surface area and excellent in conductivity through static electricity, aggregation of Ni / Sm-DHs nanoparticles is avoided, and MXene interlayer re-stacking can be prevented. The process does not need special equipment, does not depend on a solvent and is safe and simple to operate, and the prepared MXene / Ni / Sm-DHs electrochemical sensor can be used for detecting dopamine and has high sensitivity, low detection limit, wide linear range and good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sensors, and in particular to a method for preparing an electrochemical sensor of a MXene / Ni / Sm-DHs nanocomposite material. Background Art

[0002] Dopamine (DA) is a neurotransmitter with a structure similar to catechins, which exists in biological fluids such as plasma, urine, cerebrospinal fluid, tears, etc. DA concentration is closely related to cognition, learning, emotional regulation, motor control, and endocrine function. For example, a decrease in dopamine can cause Parkinson's disease, which is common in the elderly, while excessive dopamine secretion can cause some extrapyramidal diseases. Therefore, the preparation of an electrochemical sensor that can accurately detect DA is of great significance for the diagnosis of these diseases.

[0003] In the construction of electrochemical sensors, it is crucial to select suitable electrode materials. As a new type of two-dimensional material, MXene has excellent electrical conductivity and adjustable surface chemical properties, and is widely used in energy storage, catalysis, and sensors. Some transition metal and lanthanide metal hydroxides have also attracted attention due to their unique electrochemical properties. Combining these hydroxides with MXene can further improve their performance and broaden their application range. However, there are relatively few studies on double metal hydroxides formed by nickel and samarium and their applications in the field of DA detection, and the preparation methods of composite materials are still limited, with problems such as complex processes and harsh reaction conditions. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a method for preparing an electrochemical sensor of a MXene / Ni / Sm-DHs nanocomposite material. The prepared MXene / Ni / Sm-DHs electrochemical sensor can be used to detect dopamine and has high sensitivity, low detection limit, wide linear range and good stability.

[0005] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for preparing an electrochemical sensor of a MXene / Ni / Sm-DHs nanocomposite material, comprising the following steps:

[0006] S1. Preparation of MXene

[0007] The A-layer elements in the MAX phase are selectively etched by using hydrofluoric acid generated by mixing fluoride and hydrochloric acid and then washed and vacuum dried to obtain MXene two-dimensional nanosheets with a layered structure; wherein: the fluoride is one of lithium fluoride and sodium fluoride;

[0008] Preparation of S2.Ni / Sm-DHs

[0009] A nickel metal salt and a samarium metal salt are used to form an aqueous solution containing nickel and samarium metal cations, urea is added to control the solution environment, and a Ni / Sm-DHs material in the form of nano-scale spherical particles is prepared under hydrothermal conditions; wherein: the nickel metal salt is selected from NiSO4, NiSO4·6H2O, NiCl2, NiCl2·6H2O, Ni(NO3)2, Ni(NO3)2·6H2O, NiBr2, NiBr2·6H2O, Any one of Ni(CH3COO)2 and Ni(CH3COO)2·4H2O, and the samarium metal salt is any one of Sm2(SO4)3, Sm2(SO4)3·8H2O, SmCl3, SmCl3·6H2O, Sm(NO3)3, Sm(NO3)3·6H2O, SmBr3, SmBr3·6H2O, Sm(CH3COO)3, and Sm(CH3COO)3·2H2O;

[0010] S3. Preparation of MXene / Ni / Sm-DHs

[0011] MXene and Ni / Sm-DHs were made into a mixed solution, and ultrasonic stirring was performed to make the originally aggregated Ni / Sm-DHs nano-spherical particles evenly dispersed on the surface and between the layers of MXene, and the Ni / Sm-DHs adsorbed between the layers prevented the stacking of MXene layers. Finally, MXene / Ni / Sm-DHs nanocomposites were obtained after centrifugation and drying.

[0012] S4. Preparation of MXene / Ni / Sm-DHs electrochemical sensor

[0013] The MXene / Ni / Sm-DHs nanocomposite material was mixed with ethanol and deionized water to form a suspension, which was then drop-coated on the electrode surface to obtain a MXene / Ni / Sm-DHs electrochemical sensor that can be used to detect dopamine. The sensor has high sensitivity, low detection limit, wide linear range and good stability.

[0014] Preferably, the S1 step is specifically as follows: the preparation process of MXene needs to be carried out in a fume hood, first preheat 100 mL of polytetrafluoroethylene liner to 60-70°C, add 40-50 mL, 6 mol / L hydrochloric acid, slowly add 1.8 g of fluoride and 2 g of MAX, and continue stirring to react for 40-60 hours, wash the obtained precipitate with deionized water to a pH of 6-7, and then vacuum dry at 60°C for 12-18 hours, and finally collect the MXene nanosheets.

[0015] Preferably, the step S2 is specifically as follows: first, 150-250 mg NiCl2·6H2O, 50-150 mg SmCl3·6H2O, and 1-1.5 g urea are dissolved in 30-50 mL deionized water to prepare a suspension, which is sealed in a high-pressure reactor for a hydrothermal reaction at 120-150° C. for 12-18 hours, and the reactor is taken out after being cooled to room temperature, and the obtained precipitate is washed with deionized water and collected under vacuum drying conditions to obtain Ni / Sm-DHs nanoparticles;

[0016] Preferably, the S3 step is specifically as follows: the above-mentioned MXene and Ni / Sm-DHs materials are configured into a mixed solution according to the mass ratio of (20-80):(30-120), ultrasonicated for 0.5-1.5 hours, stirred for 3-12 hours, and then centrifuged, washed and dried to obtain a MXene / Ni / Sm-DHs nanocomposite material.

[0017] Preferably, the S4 step is specifically as follows: adding MXene / Ni / Sm-DHs nanocomposite material to an ethanol aqueous solution and performing ultrasonic oscillation to obtain a uniformly dispersed MXene / Ni / Sm-DHs nanocomposite suspension; then, dropping it on a pretreated electrode, and vacuum drying it at room temperature to obtain a MXene / Ni / Sm-DHs nanocomposite modified electrode, i.e., an electrochemical sensor of a MXene / Ni / Sm-DHs nanocomposite material.

[0018] Preferably, the MXene is any one of Ti-based, V-based, Cr-based, Mn-based, Fe-based, Co-based, Ni-based, Nb-based, Mo-based, Cr-based, Ta-based, and W-based MXene.

[0019] Preferably, the volume ratio of the ethanol-water solution is (1-2): (1-2), and the mass volume ratio concentration of the MXene / Ni / Sm-DHs nanocomposite material is 1-5 mg / L.

[0020] Preferably, the electrode is any one of a glassy carbon electrode, a graphite electrode, a gold electrode, a gold disk electrode, an ITO glass electrode, a screen-printed carbon electrode or a screen-printed gold film electrode.

[0021] The present invention provides a method for preparing an electrochemical sensor of a MXene / Ni / Sm-DHs nanocomposite material, which has the following beneficial effects:

[0022] 1. The present invention combines MXene with a two-dimensional nanostructure, a large specific surface area, and excellent conductivity with Ni / Sm-DHs, which is non-toxic, low-cost, and highly electrochemically active, by electrostatic self-assembly. Different from the composite method in existing research, it is only carried out under ordinary atmospheric pressure and room temperature, and has the relative advantages of not requiring special equipment, not relying on solvents, and being safe and simple to operate.

[0023] 2. The present invention utilizes the two-dimensional layered structure and large specific surface area of ​​MXene to facilitate adsorption characteristics and the structural stability, uniform morphology and size of Ni / Sm-DHs, which are conducive to attachment to the surface or between layers of MXene. The two-dimensional layered MXene is compounded with nano-spherical particles of Ni / Sm-DHs, which can not only prevent the aggregation of nanoparticles, but also prevent the restacking of MXene layers.

[0024] 3. The electrochemical sensor of the MXene / Ni / Sm-DHs nanocomposite prepared in the present invention exhibits high sensitivity, low detection limit, wide linear range, good selectivity and stability for dopamine detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The flowchart of the preparation of the electrochemical sensor of the MXene / Ni / Sm-DHs nanocomposite material in the embodiment of the present invention;

[0026] Figure 2 SEM images of MAX phase materials, MXene two-dimensional nanosheets, Ni / Sm-DHs and MXene / Ni / Sm-DHs in the embodiments of the present invention;

[0027] Figure 3 The MXene, Ni / Sm-DHs, and MXene / Ni / Sm-DHs modified GCE electrodes in the embodiments of the present invention were prepared at pH = 7.4 and a concentration of 0.1 mol·L -1 CV curves of DA with the same concentration added to phosphate buffer solution (PBS);

[0028] Figure 4 This is a DPV curve of the MXene / Ni / Sm-DHs nanocomposite modified electrode in the embodiment of the present invention when different concentrations of DA are added to the PBS solution;

[0029] Figure 5 This is a linear relationship diagram between the peak oxidation current and the DA concentration of the MXene / Ni / Sm-DHs nanocomposite material in an embodiment of the present invention;

[0030] Figure 6 This is the long-term stability test result of the MXene / Ni / Sm-DHs nanocomposite modified electrode in the embodiment of the present invention. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Embodiment 1:

[0033] The embodiment of the present invention provides a method for preparing an electrochemical sensor of a MXene / Ni / Sm-DHs nanocomposite material, comprising the following steps:

[0034] S1. Preparation of MXene

[0035] The entire preparation process needs to be carried out in a fume hood. First, a clean 100mL polytetrafluoroethylene liner is placed in a water bath for preheating. When the temperature stabilizes at 65°C, 40mL of 6mol / L hydrochloric acid is added. 1.8g of lithium fluoride and 2g of Ti3AlC2 are weighed and slowly added to the liner under stirring conditions. Then, the polytetrafluoroethylene liner is covered with a lid and stirred and heated for 48h. Finally, the precipitate is washed 9 times with deionized water, and the wet precipitate is dried in a vacuum drying oven at 60°C for 12h and collected to obtain MXene nanosheets.

[0036] Preparation of S2.Ni / Sm-DHs

[0037] First, 200 mg NiCl2·6H2O, 100 mg SmCl3·6H2O, and 1.2 g urea were dissolved in 50 mL deionized water to prepare a suspension, which was sealed in a high-pressure reactor for hydrothermal reaction at 150°C for 12 h. After the reactor was cooled to room temperature, it was taken out, and the obtained precipitate was washed with deionized water and dried under vacuum at 60°C and then collected to obtain Ni / Sm-DHs nanoparticles.

[0038] S3. Preparation of MXene / Ni / Sm-DHs

[0039] The MXene and Ni / Sm-DHs powders obtained in the above steps S1 and S2 were prepared into a mixed solution at a ratio of 50:70 (mg), subjected to ultrasonic treatment for 1 h, stirred for 6 h, and then centrifuged and washed with deionized water. Finally, the precipitate was collected under vacuum drying conditions at 60 °C to obtain MXene / Ni / Sm-DHs nanocomposites of different proportions;

[0040] S4. Preparation of MXene / Ni / Sm-DHs electrochemical sensor

[0041] Add 2 mg of MXene / Ni / Sm-DHs nanocomposite material to an ethanol-water solution with a volume ratio of 2:1 and perform ultrasonic oscillation for 30 minutes to obtain a uniformly dispersed 1 mL MXene / Ni / Sm-DHs nanocomposite suspension; then, take 10 μL and drop it on the pretreated glassy carbon electrode and dry it in vacuum at room temperature to obtain a MXene / Ni / Sm-DHs nanocomposite modified electrode, which is an electrochemical sensor of MXene / Ni / Sm-DHs nanocomposite material.

[0042] In this example, scanning electron microscopy was used to compare the morphology and microstructure of MAX, MXene, Ni / Sm-DHs, and MXene / Ni / Sm-DHs materials. Electrochemical tests were performed using a three-electrode system and the test results were analyzed. A glassy carbon electrode (with a droppable surface area of ​​0.07 cm -2 ) as the working electrode, platinum electrode as the counter electrode, silver-silver chloride electrode as the reference electrode, the electrolyte solution has a pH of 7.4 and a concentration of 0.1 mol·L -1 The test results are analyzed in conjunction with the attached drawings, as follows:

[0043] Figure 1 The preparation process of the electrochemical sensor of the MXene / Ni / Sm-DHs nanocomposite material of the present invention is as follows: the main idea is to first prepare MXene nanosheets and Ni / Sm-DHs nanoparticles, combine the two by electrostatic self-assembly to form a MXene / Ni / Sm-DHs nanocomposite material, and modify it on the working electrode to complete the preparation of the electrochemical sensor of the MXene / Ni / Sm-DHs nanocomposite material.

[0044] Figure 2 Preparation of MAX phase materials (Ti3AlC2) and MXene two-dimensional nanosheets (Ti3C2T x ), double metal hydroxide (Ni / Sm-DHs) and composite material (MXene / Ni / Sm-DHs). Figure 2 As shown in a, the original MAX phase material has an overall block structure; Figure 2 b is MXene two-dimensional nanosheet, compared with Figure 2 a It can be observed that it has an obvious layered structure; Figure 2 c: The morphology of Ni / Sm-DHs is the aggregation state of spherical nanoparticles; Figure 2 d is the composite of Ni / Sm-DHs nanoparticles adsorbed on the surface and interlayer of MXene two-dimensional nanosheets. Figure 2c It can be observed that the originally aggregated Ni / Sm-DHs nano-spherical particles are evenly dispersed on the surface and between layers of MXene, which prevents the aggregation of nanoparticles and relatively prevents the restacking of MXene layers.

[0045] Figure 3 The CV curves of MXene, Ni / Sm-DHs, and MXene / Ni / Sm-DHs modified electrodes in PBS (pH=7.4) solution after adding 200μMDA. The CV active area of ​​MXene / Ni / Sm-DHs is significantly larger than that of MXene and Ni / Sm-DHs modified electrodes, which indicates that MXene / Ni / Sm-DHs electrode has better electrocatalytic performance for the detection of DA.

[0046] Figure 4 The DPV test curve of adding different concentrations of DA to the MXene / Ni / Sm-DHs nanocomposite modified electrode in PBS solution can effectively illustrate the electrochemical sensing performance of MXene / Ni / Sm-DHs for DA. Continuously adding linear concentrations of DA to PBS (pH = 7.4) solution, with the increase of DA concentration (0.05 ~ 60μM), the oxidation peak current increases, indicating that MXene / Ni / Sm-DHs material has good detection performance for DA.

[0047] Figure 5 The relationship between the peak current of the MXene / Ni / Sm-DHs nanocomposite and the DA concentration is shown in Figure 2. The fitted linear relationship is divided into two sections. At low concentrations of DA (0.05-10 μM), the linear fitting equation is I = 0.31039C + 1.53162 (R 2 =0.996), at high concentrations (10-60 μM), the linear fitting equation is I = 0.0858C + 3.84432 (R 2 =0.992). The minimum detection limit obtained by the linear fitting equation is 11.47nM (S / N=3), and the sensitivity is 4.434μA·μM -1 cm -2 , the linear range is 0.01~60μM.

[0048] Figure 6 The long-term stability test results of the MXene / Ni / Sm-DHs nanocomposite modified electrode of the present invention are shown in Figure 2. The stability of the MXene / Ni / Sm-DHs electrode was evaluated by DPV test, and its amperometric response was observed by adding 100 μM to PBS for 30 days, indicating that the electrochemical sensor has a good and stable amperometric response and a long sensing time.

[0049] In summary, the present invention combines two-dimensional layered MXene with nano-spherical particles of Ni / Sm-DHs, which not only avoids the aggregation of Ni / Sm-DHs nanoparticles, but also prevents the restacking of MXene layers. The process does not require special equipment, does not rely on solvents, and is safe and simple to operate. The prepared MXene / Ni / Sm-DHs electrochemical sensor can be used to detect dopamine, and has high sensitivity, low detection limit, wide linear range and good stability.

[0050] Embodiment 2:

[0051] The embodiment of the present invention provides a method for preparing an electrochemical sensor of a MXene / Ni / Sm-DHs nanocomposite material, comprising the following steps:

[0052] S1. Preparation of MXene

[0053] The entire preparation process needs to be carried out in a fume hood. First, a clean 100mL polytetrafluoroethylene liner is placed in a water bath for preheating. When the temperature stabilizes at 65°C, 40mL of 6mol / L hydrochloric acid is added. 1.8g of lithium fluoride and 2g of Ti3AlC2 are weighed and slowly added to the liner under stirring conditions. Then, the polytetrafluoroethylene liner is covered with a lid and stirred and heated for 48h. Finally, the precipitate is washed with deionized water until the pH value is neutral. The wet precipitate is dried in a vacuum drying oven at 60°C for 12h and then collected to obtain MXene nanosheets.

[0054] Preparation of S2.Ni / Sm-DHs

[0055] First, 200 mg NiCl2·6H2O, 100 mg SmCl3·6H2O, and 1.2 g urea were dissolved in 50 mL deionized water to prepare a suspension, which was sealed in a high-pressure reactor for hydrothermal reaction at 150 °C for 12 h. After the reactor was cooled to room temperature, it was taken out, and the obtained precipitate was washed with deionized water several times and dried under vacuum at 60 °C and collected to obtain Ni / Sm-DHs nanoparticles.

[0056] S3. Preparation of MXene / Ni / Sm-DHs

[0057] The MXene and Ni / Sm-DHs powders obtained in the above steps S1 and S2 were prepared into a mixed solution in a ratio of 50:70 (mg), ultrasonicated for 1 h, stirred for 6 h, and then the precipitate was centrifuged and washed several times with deionized water, and finally collected under vacuum drying conditions at 60 ° C to obtain MXene / Ni / Sm-DHs nanocomposites with different ratios;

[0058] S4. Preparation of MXene / Ni / Sm-DHs electrochemical sensor

[0059] Add 2 mg of MXene / Ni / Sm-DHs nanocomposite material to an ethanol-water solution with a volume ratio of 2:1 and perform ultrasonic oscillation for 30 minutes to obtain a uniformly dispersed 1 mL MXene / Ni / Sm-DHs nanocomposite suspension; then, take 10 μL and drop it on the pretreated glassy carbon electrode and dry it in vacuum at room temperature to obtain a MXene / Ni / Sm-DHs nanocomposite modified electrode, which is an electrochemical sensor of MXene / Ni / Sm-DHs nanocomposite material.

[0060] Comparative Example 1:

[0061] Comparative Example 1 adopts “Electrochemical sensing of dopamine using a Ni-based metal-organic framework modified electrode” proposed by Huang, Z; Zhang, L et al. in “Lonics”.

[0062] Comparative Example 2:

[0063] Comparative Example 2 adopts the “Perylene diimide / MXene-modified graphitic pencil electrode-based electrochemical sensor for dopamine detection” proposed by Amara, U; Mehran, M et al. in “Microchimica Acta”.

[0064] Comparative Example 3:

[0065] Comparative Example 3 adopts the “Photo-electrochemical detection of dopamine in human urine and calf serum based on MIL-101(Cr) / carbon black” proposed by Li, Z; Zhang, H et al. in “Microchimica Acta”.

[0066] Comparative Example 4:

[0067] Comparative Example 4 adopts "Fe3O4 nanorods decorated on polypyrrole / reduced graphene oxide for electrochemical detection of dopamine and photocatalytic degradation of acetaminophen" proposed by Santhosh Kumar, R; Govindan, K et al. in "Applied Surface Science".

[0068] Comparative Example 5:

[0069] Comparative Example 5 adopts the “Simultaneous Detection of Dopamine, Uric Acid and α-Lipoic Acid Using Nickel Hydroxide Nanosheets” proposed by Mary Tomy, A; Cyriac, J et al. in “Microchemical Journal”.

[0070] Comparative Example 6:

[0071] Comparative Example 6 adopts "Designing C-Fe-O bonded MIL-88B(Fe) / jasmine petal-derived-carbon composite biosensor for the simultaneous detection of dopamine anduric acid" proposed by Qu, Z; Muhammad, Y et al. in "Chemical Engineering Journal".

[0072] The electrochemical sensor prepared in Example 1 of the present invention was compared with Comparative Examples 1 to 6. The results are shown in Table 1. The results show that the MXene / Ni / Sm-DHs nanocomposite modified electrode disclosed in the present invention has the advantages of low detection limit, high sensitivity and wide linear range for DA detection. The specific contents of Table 1 are as follows:

[0073] Table 1 Comparison of analytical performance of different modified electrodes for detecting DA

[0074]

[0075] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an electrochemical sensor of a MXene / Ni / Sm-DHs nanocomposite material, characterized in that: The following steps are involved: S1. Preparation of MXene The A-layer elements in the MAX phase were selectively etched by using hydrofluoric acid generated by mixing fluoride and hydrochloric acid, and MXene two-dimensional nanosheets with a layered structure were obtained after washing and vacuum drying. Preparation of S2.Ni / Sm-DHs The Ni / Sm-DHs material with nano-scale spherical particle aggregation morphology was prepared under hydrothermal conditions by using nickel metal salt and samarium metal salt to form an aqueous solution containing nickel and samarium metal cations, adding urea to control the solution environment. S3. Preparation of MXene / Ni / Sm-DHs MXene and Ni / Sm-DHs were made into a mixed solution, and ultrasonic stirring was performed to make the originally aggregated Ni / Sm-DHs nano-spherical particles evenly dispersed on the surface and between the layers of MXene, and the Ni / Sm-DHs adsorbed between the layers prevented the stacking of MXene layers. Finally, MXene / Ni / Sm-DHs nanocomposites were obtained after centrifugation and drying. S4. Preparation of MXene / Ni / Sm-DHs electrochemical sensor The MXene / Ni / Sm-DHs nanocomposite material was mixed with ethanol and deionized water to form a suspension, which was then drop-coated on the electrode surface to obtain a MXene / Ni / Sm-DHs electrochemical sensor that can be used to detect dopamine.

2. The preparation method according to claim 1, characterized in that: The specific steps of S1 are as follows: The preparation process of MXene needs to be carried out in a fume hood. First, preheat 100mL of polytetrafluoroethylene liner to 60-70°C, add 40-50mL, 6mol / L hydrochloric acid, slowly add 1.8g of fluoride and 2g of MAX, and continue to stir the reaction for 40-60h. Wash the obtained precipitate with deionized water to a pH of 6-7, and then vacuum dry it at 60°C for 12-18h to finally collect the MXene nanosheets.

3. The preparation method according to claim 1, characterized in that: The specific steps of step S2 are as follows: first, 150-250 mg NiCl2·6H2O, 50-150 mg SmCl3·6H2O, and 1-1.5 g urea are dissolved in 30-50 mL deionized water to prepare a suspension, which is sealed in a high-pressure reactor for a hydrothermal reaction at 120-150° C. for 12-18 h. After the reactor is cooled to room temperature, it is taken out, and the obtained precipitate is washed with deionized water and collected under vacuum drying conditions to obtain Ni / Sm-DHs nanoparticles.

4. The preparation method according to claim 1, characterized in that: Step S3 is as follows: prepare the above MXene and Ni / Sm-DHs materials into a mixed solution at a mass ratio of (20-80):(30-120), ultrasonicate for 0.5-1.5h, stir for 3-12h, and then centrifuge, wash, and dry to obtain a MXene / Ni / Sm-DHs nanocomposite material.

5. The preparation method according to claim 1, characterized in that: The specific steps of step S4 are as follows: add MXene / Ni / Sm-DHs nanocomposite material to ethanol aqueous solution and perform ultrasonic oscillation to obtain a uniformly dispersed MXene / Ni / Sm-DHs nanocomposite suspension; then, drop it on the pretreated electrode and dry it under vacuum at room temperature to obtain a MXene / Ni / Sm-DHs nanocomposite modified electrode, which is an electrochemical sensor of MXene / Ni / Sm-DHs nanocomposite material.

6. The preparation method according to claim 4, characterized in that: The MXene is any one of Ti-based, V-based, Cr-based, Mn-based, Fe-based, Co-based, Ni-based, Nb-based, Mo-based, Cr-based, Ta-based, and W-based MXenes.

7. The preparation method according to claim 5, characterized in that: The volume ratio of the ethanol-water solution is (1-2): (1-2), and the mass volume ratio concentration of the MXene / Ni / Sm-DHs nanocomposite material is 1-5 mg / L.

8. The preparation method according to claim 1 or 5, characterized in that , the electrode is any one of a glassy carbon electrode, a graphite electrode, a gold electrode, a gold disk electrode, an ITO glass electrode, a screen-printed carbon electrode or a screen-printed gold film electrode.

9. The preparation method according to claim 1, characterized in that: The fluoride is one of lithium fluoride and sodium fluoride.

10. The preparation method according to claim 1, characterized in that: The nickel metal salt is selected from any one of NiSO4, NiSO4·6H2O, NiCl2, NiCl2·6H2O, Ni(NO3)2, Ni(NO3)2·6H2O, NiBr2, NiBr2·6H2O, Ni(CH3COO)2, and Ni(CH3COO)2·4H2O, and the samarium metal salt is selected from any one of Sm2(SO4)3, Sm2(SO4)3·8H2O, SmCl3, SmCl3·6H2O, Sm(NO3)3, Sm(NO3)3·6H2O, SmBr3, SmBr3·6H2O, Sm(CH3COO)3, and Sm(CH3COO)3·2H2O.

Citation Information

Patent Citations

  • Dopamine detection electrochemical sensor based on nano-porous MXene material

    CN118191061A